Evaluation Of Pdms-Based Uv-Crosslinked Hydrogels Properties For Tissue Engineering Applications - Lim, Kar Wai (2018)
This work presents the fabrication of PDMS-based hydrogels with tunable properties via direct blending. Two UV-crosslinkable PDMS with different molecular weights (Mn=1k & 6k g/mol) were first synthesized and then UV-cured with PEGDA (Mn=0.7k g/mol) at various wt.% ratio, in the presence of Irgacure as photoinitiator. For the medium Mn PDMS (6k), allyl methacrylate (AMA) was used as reactive modifier to enhance compatibility of the two highly immiscible polymers. The liquid mixtures were converted into hydrogels after exposed to UV irradiation at a wavelength region of 315-400 nm at the average intensity of 10 mW/cm2 for 30 minutes. Compatibility, thermal, swelling, wetting, mechanical, protein adsorption and cytotoxicity properties of these PDMS hydrogels were evaluated. From differential scanning calorimetry (DSC) study, although two Tg were observed in the hydrogels fabricated from the low Mn PDMS (1k), they were all compatible since the hydrogel surface was homogeneous at any PEG wt.% ratio, as supported by AFM result. The hydrogels fabricated from the PDMS (6k) were highly incompatible and this was especially the case for the 30 wt.% PEG with the occurrence of macrophase separation. This problem was solved with addition of AMA. The phase separation of these PDMS (6K) hydrogels affected other properties in which the more hydrophobic gel surface, after the addition of AMA, had lowered their swelling and wetting properties since there was a fewer amount of PEG domains to render the hydrophilic surface. Protein adsorption to these hydrogel was higher if the surface was dominated by the PDMS surfaces, yet the adsorption was still lower than the bare PDMS. Stiffness of the hydrogel was fall within an acceptable range of soft tissue at ~ 0.5-1 MPa, with the stiffness increased with the increased of PEG loading, and/or the decreased of AMA loading. Coupled with their non-cytotoxic property, the fabricated PDMS-based hydrogels could potentially be used as scaffolds for tissue engineering applications.